1 Multiply both sides by 3 .

\[

(v+2)^{2}-6=1 \times 3

\]

2 Simplify \(1 \times 3\) to 3 .

\[

(v+2)^{2}-6=3

\]

(3) Add 6 to both sides.

\[

(v+2)^{2}=3+6

\]

4) Simplify \(3+6\) to 9 .

\[

(v+2)^{2}=9

\]

5 Take the square root of both sides.

\[

v+2=\pm \sqrt{9}

\]

6 Since \(3 \times 3=9\), the square root of 9 is 3 .

\[

v+2=\pm 3

\]

7. Break down the problem into these 2 equations.

\[

\begin{aligned}

&v+2=3 \\

&v+2=-3

\end{aligned}

\]

\(\mathbf{8}\) Solve the 1 st equation: \(v+2=3\).

\[

v=1

\]

9 Solve the 2 nd equation: \(v+2=-3\).

\[

v=-5

\]

10 Collect all solutions.

\[

v=1,-5

\]